New records of polychaetes (Annelida) for northern Ecuador - Trovant, Berenice (2012)
Even though Ecuador is one of the twelve mega-diverse countries in the world, the polychaetes are still poorly known. Twelve polychaete species, namely Hemipodia pustatula (Glyceridae); Microphthalmus arenarius (Hesionidae); Scoletoma zonata (Lumbrineridae); Nereis riisei, Pseudonereis gallapagensis (Nereididae); Armandia salvadoriana, Euzonus mucronata (Opheliidae); Phyllodoce multiseriata (Phyllodocidae); Pisione longispinulata (Pisionidae); Malacoceros indicus, Scolelepis (Scolelepis) acuta (Spionidae) and Opisthosyllis arboricola (Syllidae) are newly reported in the intertidal sandy beaches of Bunche (0°39´01.98´´N 80°03´55.01´´W) and Cabo San Francisco (0°38´16.35´´N 80°03´14.07´´W), Esmeraldas Province (Ecuador). Furthermore, an amended diagnosis of Pisione longispinulata is presented.